2002
DOI: 10.1111/1467-9299.00295
|View full text |Cite
|
Sign up to set email alerts
|

Contingent and Non‐Contingent Working in Local Government: Contrasting Psychological Contracts

Abstract: Given that the contingent worker is likely to be a familiar presence in the public service workplace of the future, this paper explores the consequences of contingent work arrangements on the attitudes and behaviour of employees using the psychological contract as a framework for analysis. Drawing upon survey evidence from a sample of permanent, fixed term and temporary staff employed in a British local authority, our results suggest that contract status plays an important role in how individuals view the exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(115 citation statements)
references
References 52 publications
6
104
0
5
Order By: Relevance
“…Semi-structured interviews provide the best means of data collection because they allow appropriate exploration of key issues (Neuman, 2000;Babbie, 1992). To ensure consistency with the literature a 17 item scale of psychological contract breach, based on measures established in the literature, was used (Coyle-Shapiro & Kessler, 2002;Lester, Turnley, Bloodgood & Bolino, 2002;Turnley & Feldman, 2000). As this is exploratory qualitative research, the researcher tape-recorded the explanations given for each score and it is these comments that form the basis of the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Semi-structured interviews provide the best means of data collection because they allow appropriate exploration of key issues (Neuman, 2000;Babbie, 1992). To ensure consistency with the literature a 17 item scale of psychological contract breach, based on measures established in the literature, was used (Coyle-Shapiro & Kessler, 2002;Lester, Turnley, Bloodgood & Bolino, 2002;Turnley & Feldman, 2000). As this is exploratory qualitative research, the researcher tape-recorded the explanations given for each score and it is these comments that form the basis of the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, these studies have demonstrated that TAWs develop a social employment exchange relationship, reciprocated with positive responses towards the client organization (Coyle-Shapiro & Kessler, 2002;Kuvaas & Dysvik, 2009;McDonald & Makin, 2000;Van Dyne & Ang, 1998). The development of a social exchange depends on how TAWs are treated by the client company (Gallagher & Connelly, 2008).…”
mentioning
confidence: 99%
“…According to studies, the level of organizational commitment of contingent employees varied: lower than permanent employees (Coyle-Shapiro & Kessler, 2000;Van Dyne & Ang, 1998), higher (McDonald & Makin, 2000 or equal to them (Pearce, 1993). These mixed results suggest that several personal, organizational factors were related to their commitment (Coyle-Shapiro & Kessler, 2002). For example, contingent employees showed more commitment and engagement when they were treated fairly and when appropriate organizational support was provided (Liden, Wayne, Kraimer, & Sparrowe, 2003).…”
Section: Organizational Commitmentmentioning
confidence: 99%